The Power of Media and the Power over Media - Todorov, Petko (Research Papers, 2014)
The study examines the ambivalent role of media as instruments of power and power control levers. Accordingly, the study evolves around questioning the power of media, on the one hand; and the power over media, on the other.The object of the study is the post-1989 period of political transition of Bulgarian media.The subject matter of the study is the capacity of the “fourth estate” to realize political media projects, as well as the political and economic power applied over media.The study aims to demonstrate that media’s social role is increasing; to reveal media’s power; and to show how political and business organizations control media in order to realize functions of political power.These points of intersection are examined theoretically and in the context of the transition years of Bulgarian media. The study outlines various dependencies and drawbacks, examines Bulgaria’s progress towards European media standards, and discusses the possible future of Bulgarian media space. In this regard, the study’s main objective is to shed further light on the specific nature of media and to differentiate the concrete parameters of their being an instrument of political power.
Keywords: Media; Power; Politics; Parties; Freedom of speech; Media politics; Media standards; Regulation; Media political projects